The influence of a child's temperament on an attention deficit - Ahn, Youngmi; Jung Yoo, Eun (Opción, 2019)
The purpose of this study is to investigate the relationship between the temperament of the child and the disability related to attention deficit via a study of descriptive correlation as a method. As a result, all the assumptions of the regression equation are satisfied, and the regression results are reliable. In conclusion, the Persistence temperament of children affecting attention disorder could be developed through basic human desire such as regular eating, securing space for activities, and exercise.